Signal Amplification by Reversible Exchange (SABRE): From Discovery to Diagnosis. Issue 23 (27th April 2018) - Rayner, Peter J.; Duckett, Simon B.
Abstract: Signal amplification by reversible exchange (SABRE) turns typically weak magnetic resonance responses into strong signals making previously impractical measurements possible. This technique has gained significant popularity because of its speed and simplicity. This Minireview tracks the development of SABRE from the initial hyperpolarization of pyridine in 2009 to the point in which 50 % 1 H polarization levels have been achieved in a di‐deuterio‐nicotinate, a key step in the pathway to potential clinical use. Simple routes to highly efficient 15 N hyperpolarization and the creation of hyperpolarized long‐lived magnetic states are illustrated. To conclude, we describe how the recently reported SABRE‐RELAY approach offers a route for parahydrogen to hyperpolarize a much wider array of molecular scaffolds, such as amides, alcohols, carboxylic acids, and phosphates, than was previously thought possible. We predict that collectively these developments ensure that SABRE will significantly impact on both chemical analysis and the diagnosis of disease in the future. Abstract : SABRE‐rattling : Signal amplification by reversible exchange (SABRE) is a hyperpolarization technique that dramatically enhances magnetic resonance signals. This Minireview tracks its development since its discovery in 2009 and offers an outlook on its potential use for both analytic sciences and disease diagnosis.